2016
DOI: 10.18869/acadpub.cmm.2.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Hyphal wall protein 1 gene: A potential marker for the identification of different Candida species and phylogenetic analysis

Abstract: Background and Purpose:Hyphal wall protein 1 (HWP1) is an important adhesin which usually is expressed on the germ tube and hyphal surface produced by different Candida species. The hyphal wall protein-coding gene (HWP1) was evaluated as a novel identification and phylogenetic marker in Candida tropicalis, C. orthopsilosis, C. parapsilosis and C. glabrata.Materials and Methods:Initially, four specific primer pairs were designed, and the target was amplified and finally sequenced. A total of 77 Candida isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The sequence difference count matrix of BT2 gene observed among the members of C. parapsilosis complex indicated that this locus may be more useful than ITS regions (84.7% versus 89.6% similarity) for the discrimination of these three closely related species (data not shown). Meanwhile, the analysis of the hyphal wall protein 1 ( HWP1 ) nucleotide sequence alignment revealed only 60% similarity between C. parapsilosis and C. orthopsilosis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sequence difference count matrix of BT2 gene observed among the members of C. parapsilosis complex indicated that this locus may be more useful than ITS regions (84.7% versus 89.6% similarity) for the discrimination of these three closely related species (data not shown). Meanwhile, the analysis of the hyphal wall protein 1 ( HWP1 ) nucleotide sequence alignment revealed only 60% similarity between C. parapsilosis and C. orthopsilosis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the targets currently explored for detection of this species in the clinical setting, hyphal wall protein 1 (HWP1), a hypha-specific cell wall protein with adhesive properties, has been suggested to be a good marker for species identification (222). The cell wall ␤-1,3-glucan content has been used to discriminate fungal cells growing in a planktonic stage from those forming biofilms.…”
Section: Cell Wall Assemblymentioning
confidence: 99%
“…The identification of C. albicans species complex (i.e., C. africana, C. albicans, and C. dubliniensis) was accomplished using the partial amplification of hyphal wall proteins (HWP1) gene according to the primers designed by Romeo and Criseo (forward, 5′-GCTACCACTTCAGAATCATCATC-3′ and reverse 5′-GCACCTTCAGTCGTAGAGACG-3′) that generate the fragments of 940 and 740 bp for C. albicans and C. africana [22]. The discrimination of C. parapsilosis complex, including C. parapsilosis and C. orthopsilosis, was conducted as previously described [23].…”
Section: Molecular Identificationmentioning
confidence: 99%